Community development and social welfare through entrepreneurship management training - Hairunisya, Nanis; Rindrayani, Sulastri Rini; Subiyantoro, Hari (Asian Management and Business Review, 2023)
The uneven distribution of superior human resources, which alienates some communities and contributes to the issue of business management literacy in SMEs, is one of the obstacles to community development. The purpose of this study is to evaluate the impact of community empowerment through literacy-based entrepreneurship management training. With a sample of 98 participants, this study use participatory action research (PAR). To select training participants, sampling method is purposive sampling with the criteria used: (1) Indonesian Manpower (TKI) who no longer work abroad; (2) Existing micro or small business owners; and (3) Trainees who have been mentored for at least one year. Methods of question and answer, observation, or questionnaires are used to obtain the data including focus group discussion (FGD), in-depth interviews, and strategies for exchanging stories, and pretest and post-test; behavioral analysis and participatory assessment analysis using percentages and likert scales; and data analysis of training success. This study is new because it explores specifically how to organize, execute, and value manufacturing innovation, inventive marketing, financial management, administrative control, financial reporting, teamwork, and business networking. It was determined that this training is helpful in increasing participants' awareness to fall into the very good category and increasing their knowledge and abilities. This finding is consistent with the notion of resource mobilization in support of human empowerment and human resource development theory, which argues that training is a process of improvement to deal with dynamic change. Government organizations can use this information to improve training programs to increase community engagement.